Materialistic Value Orientation and Attitude toward Environmental Management in Yakurr Local Government Area of Cross River State, Nigeria: Implication for Social Studies Education - Essien, Essien Ekpenyong; Essien, Cecilia K.; Ojong, Aganyi Asu; Owan, Lucy Alorye; Obot, Imo M. (Mediterranean Journal of Social Sciences, 2020)
This investigation examined materialistic value orientation and attitude toward environmental management in Yakurr Local Government Area of Cross River State, Nigeria. A single theory was generated to control the examination. Review of initial researches was utilized. Survey blue print was utilized. An accidental sampling technique was used in choosing the 150 persons examined for the investigation. An approved 20 items four point adjusted likert scale poll was the instrument utilized for data assortment. The unwavering quality gauge of the tool for information accumulation was 0.80 utilizing Cronbach Alpha dependability technique. The information was dissected utilizing the simple and multiple linear regression statistical tools. The result of the study revealed that there is a significant influence of materialistic value orientation and attitude toward environmental management in Yakurr Local Government Area. It was recommended that People limit their rate of materialism, it is conceivable to get those people to consider more to be well disposed ways of life as a suitable and appealing decision.